The possible effects of COVID-19 on the human reproductive system - Dağdeviren, Tuğba; Yolcu, Hatice Kübra (The European Research Journal, 2023)
Spike surface glycoprotein and small envelope matrix-nucleocapsid proteins, is from the Coronaviridae family and binds to host receptors via spike surface proteins. Although it shows its symptoms especially on the respiratory tract, various studies have been carried out considering that it also affects other systems in the body. For the virus to enter the host cell, it must bind to ACE2 (angiotensin converting enzyme 2). ACE2 is a key protein involved in balancing Ang I and Ang II levels. With receptors such as TMPRSS2 (transmembrane serine protease 2), the effects of the virus on the human reproductive system are much better understood. Since human germ cells and early embryos express ACE2, there is a potential risk of the Coronavirus associated with germ cells. Studies show that the coronavirus changes the amount and density of hormones in the human reproductive system. The fact that most of the partners of 35 female patients who had SARS-CoV-2 in the studies were infected individuals suggests that sexual transmission may be possible. It was determined that TMPRSS4, Cathepsin B and L, FURIN, MX1 and BSG gene expressions were high in the menstrual cycle, while ACE 2 and TMPRSS2 were moderately expressed. It has been shown that the ACE2 enzyme is most intensely expressed is the testes. Studies have shown that sperm DNA (deoxyribonucleic acid) fragmentation, changes in hormone levels and the formation of anti-sperm antibodies are an important cause of male infertility. Infected men have been found to have an impaired spermatogenesis. This rewiew; it aims to draw attention to the possible effects of the corona virus on the human reproductive system and to reveal new mechanisms for new research to be done.